Managing Inventory Systems Using Optimization - Alema-Mensah, Ernest (2011)
A Thesis Submitted to the Department of Mathematics, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfillment of the requirement for the degree of Master of Science in Industrial Mathematics, Institute of Distance Learning.